2014
DOI: 10.1038/ejhg.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotypic spectrum of PORCN variants in two males with syndromic microphthalmia

Abstract: Variants in PORCN are a cause of Goltz-Gorlin syndrome or Focal Dermal Hypoplasia, an X-linked dominant disorder affecting heterozygous females and until now considered to be embryonic lethal in males. Exome sequencing was performed in a family in which two male siblings were characterized by microphthalmia and additional congenital anomalies including diaphragmatic hernia, spina bifida and cardiac defects. Surprisingly, we identified a maternally inherited variant in PORCN present in both males as well as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
2
15
1
Order By: Relevance
“…Of the 24 reported male patients, 19 are mosaics, one patient has Klinefelter syndrome, and four patients from two different families are non‐mosaics (Table 1). Interestingly, all four patients with non‐mosaic PORCN mutations lacked skin manifestations but had other severe symptoms compatible with GS 20, 21. In addition, diaphragm abnormalities were detected in two patients, resembling previously reported cases with pentalogy of Cantrell 18, 22…”
Section: Discussionsupporting
confidence: 84%
“…Of the 24 reported male patients, 19 are mosaics, one patient has Klinefelter syndrome, and four patients from two different families are non‐mosaics (Table 1). Interestingly, all four patients with non‐mosaic PORCN mutations lacked skin manifestations but had other severe symptoms compatible with GS 20, 21. In addition, diaphragm abnormalities were detected in two patients, resembling previously reported cases with pentalogy of Cantrell 18, 22…”
Section: Discussionsupporting
confidence: 84%
“…A recently published whole-exome sequencing study has also reported two non-mosaic males with clinical symptoms overlapping FDH with an inherited mutation in the PORCN gene [31]. Both male patients in this study had a c.407G > A mutation change resulting in a Glycine to Aspartate amino acid change in the protein which is different from the variant and amino acid change that we report here.…”
Section: Discussioncontrasting
confidence: 45%
“…There have been 3 clinical reports of male patients who are nonmosaic for PORCN mutations [Brady et al, 2015;Madan et al, 2017]. Two of these patients, who deceased in their neonatal periods, had a single base pair alteration resulting in a missense mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these patients, who deceased in their neonatal periods, had a single base pair alteration resulting in a missense mutation. Interestingly, their mother and 2 female siblings also had the same mutation without clinical symptoms of FDH as a result of skewed X inactivation [Brady et al, 2015]. The third patient had a missense mutation in PORCN and died at the age of 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation